Single-plane dual-modality tomography for multiphase flow imaging by integrating electrical capacitance and ultrasonic sensors - Pusppanathan, Jaysuman; Abdul Rahim, Ruzairi; Phang, Fatin Aliah; Mohamad, Elmy Johana; Nor Ayob, Nor Muzakkir; Rahiman, Mohd Haﬁz Fazalul; Chan, Kok Seong (IEEE, 2017)
This paper presents an experimental study of a single-plane dual-modality tomography (DMT) system integrat-ing electrical capacitance tomography (ECT) and ultrasonic tomography (UT) for water–oil–gas three-phase ﬂow imaging. The soft-ﬁeld (ECT) and hard-ﬁeld (UT) systems measure differ-ent physical parameters, making them both a ﬁne combination in complementing each system’s limitations. The DMT system consists of 16 units of customized ECT sensors and 16 units of UT transducers, which are composited on a single-plane arrange-ment to perform concurrent measurement. A ﬁnite-element method is used to model and study its feasibility and performance before engaging with the actual hardware. The DMT system is carried out on a vertical test column and horizontal stratiﬁed ﬂow to obtain sensor data from each modality by inspection of separate tomographic image using linear back-projection (LBP) image reconstruction algorithm and convolution back projection with Gaussian ﬁltering (CBPF). A fuzzy logic pixel fusion method is used for image fusion process. To evaluate the reconstructed images, the mean structural similarity index (MSSIM) method and the mutual information method (MF) are employed on both the LBP and CBPF image results. The analysis and assessments proved that the CBPF method has successfully improvised the image results and thus has better MSSIM rating and MF over the LBP method with an enhancement up to 12.55% and 8.92%, respectively.